Long-Term Care Regulations in Ontario, Canada during COVID-19 - Steve Hunt; Elena Hunt (European Scientific Journal, ESJ, 2021)
The Ontario, Canada statutory requirements of Nurse Patient ratios and other Health care professionals’ activities are discussed following a descriptive, analytical and investigative approach. Using OECD Statistics and evaluating the impact on population health during COVID-19, as well as drawing from constitutional law and administrative law, the authors apply, explain and clarify opinions of jurists, rulings of judges and arbitrators and pull comparisons to statutory and statistical data from international jurisdictions such as Australia and USA. Recommendations for improvement of the Ontario Health Care system are conferred.